Pengujian Model Kinerja Keuangan Pada UMKM Di Kabupaten Buleleng - Komang Eni Candraningsih; Anantawikrama Tungga Atmadja; Desak Nyoman Sri Werastuti (Universitas Pendidikan Ganesha, 2023)
Abstract This research is based on the decline in the financial performance of MSMEs in the Buleleng Regency. This study aimed to empirically prove the effect of financial literacy and financial technology on financial inclusion and its impact on the financial performance of MSMEs in the Buleleng Regency. The sample of this research is MSMEs in Buleleng Regency, which was selected using the purposive sampling method. Data analysis used Structural Equation Modeling-Partial Least Square with the help of SmartPLS Version 3. The results showed that financial literacy and financial technology positively and significantly affected financial inclusion. Financial literacy and financial technology positively and significantly affected financial performance. Financial inclusion had a positive and significant effect on financial performance, and financial inclusion mediates the effect of financial literacy and financial technology on financial performance. Keywords: financial performance; financial inclusion; financial literacy; financial technology.